Therapeutic implications of Traditional Music in Neonatal Care: A review of Empirical Data - N.U., Ramachandra; Ramamishra Yashaswi, M.; D C, Shivakumara (Journal of Neonatal Surgery, 2025)
Indian traditional music based largely on the Marga and Desi traditions-has a potential therapeutic application in NICUs. Indian classical ragas and lullabies are culturally important and possess structured tonal systems. Many research scholars have attempted to explore music therapy with empirical studies. In this article it is attempted to collect the empirical data and across research data base including the PubMed, Cochrane, Scopus and Peer-reviewed journals. This is an attempt to integrate understanding of numerous studies focusing on the physiological, developmental, and stress-reducing effects on both preterm and term infants. The existing studies are analyzed to point out gaps in methodology, and suggest ways to help integrate Indian music into protocols of neonatal care